Effect of Spectral Quality of Monochromatic LED Lights on the Growth of Artichoke Seedlings - Rabara, Roel C.; Behrman, Glenn; Timbol, Thomas; Rushton, Paul J. (Frontiers in Plant Science, 2017)
Indoor farming is becoming a popular alternative approach in food production to meet the demand of a growing world population. Under this production system, artificial light provides the main source of illumination in sustaining plant growth and development. The use of light-emitting diodes (LEDs) is a popular source of artificial light for indoor farms due to its modular design and energy efficiency. The purpose of this study is to assess the effect of LED light quality in the growth of artichoke seedlings. Three genotypes of artichoke were grown under red, white and blue LEDs. Their growth was compared to identical artichokes grown under natural light in a greenhouse. The spectral quality of each light treatment was measured. Phenotypic characters such as plant height, root length, shoot/root biomass as well as the chlorophyll content were measured. Digital image analysis was performed to assess the greenness of artichoke seedlings under various light treatments. The results show that photosynthetic photon flux density (PPFD) was highest under red LED light, but only a third compared to the total PPFD under natural light. Under red light, plant height, root length, biomass, and chlorophyll content was higher compared to other light treatments. This study showed that red light significantly influenced the growth and development of the artichoke seedlings.